Implementasi Kebijakan Penempatan dan Perlindungan TKI di Luar Negeri oleh BP3TKI Provinsi Jawa Tengah - Maulida Rahmawati Putri; Hartuti Purnaweni; Soedjono Soedjono (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2019)
This paper describes and analyzes the process of implementing the Law No.39 of 2004 concerning the Placement and Protection of Indonesian Migrant Workers Abroad by BP3TKI, Central Java Province. Then identify the driving and inhibiting factors, and provide recommendations on obstacles. This research is a qualitative research with descriptive analysis. The technique of collecting data is done by interview, observation, literature study, and documentation. The problems that arise in the implementation of the policy of Placement and Protection of Indonesian Migrant Workers Abroad by BP3TKI Central Java emphasize more on the implementation process which will only be accurate with a qualitative approach. Theory analysis used in this study, namely the model of policy implementation by George C. Edwards III with indicators: communication, resources, disposition, and bureaucratic structure.              The results showed that there were several obstacles in the implementation of this policy, such as (1) BP3TKI knew that PPTKIS did not carry out psychological examinations, but there was no further action, (2) BP3TKI stated that PPTKIS sometimes did not report migrant workers, making it difficult for BP3TKI to carry out protection , (3) PPTKIS considers that human resources in the district / city offices of TKI originating services to prospective TKIs are less responsive.              Recommendations that can be given for this study include: (1) BP3TKI must provide evaluation and sanctions on the process of health and psychology examinations for prospective migrant workers who will depart because based on information from the PPTKIS the designated clinics have never conducted psychology examinations for prospective TKI; (2) Tightening the rules for reporting of residence changes to Indonesian migrant workers at the time of placement and imposing sanctions for those who violate; (3) Regular coordination is not enough between BP3TKI and the District / City Service, there must be changes regarding the service policy towards the management of prospective migrant workers so that the services of the District / City Service are not slow and there are no delays that drag on.